2015
DOI: 10.1186/s12967-015-0429-9
|View full text |Cite
|
Sign up to set email alerts
|

Inducibility of ventricular fibrillation during mild therapeutic hypothermia: electrophysiological study in a swine model

Abstract: Introduction: Mild therapeutic hypothermia (MTH) is being used after cardiac arrest for its expected improvement in neurological outcome. Safety of MTH concerning inducibility of malignant arrhythmias has not been satisfactorily demonstrated. This study compares inducibility of ventricular fibrillation (VF) before and after induction of MTH in a whole body swine model and evaluates possible interaction with changing potassium plasma levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 47 publications
(36 reference statements)
1
4
0
2
Order By: Relevance
“…Combined analysis of the RAPID MI-ICE and the CHILL-MI trials also exhibited no difference in atrial fibrillation incidence ( 24 ). Within the temperature range used in STEMI cooling studies, no significant increase in ventricular arrhythmias has been reported ( 22 , 24 ), a finding consistent with animal studies ( 25 ). Taken together, mild TH seems not to significantly increase the occurrence of arrhythmia in general STEMI patients, but there could be a subpopulation of patients more prone to the development of arrhythmias, such as those with electrolyte dysregulation.…”
Section: Ecg Changes and Arrhythmias Associated With Thsupporting
confidence: 79%
“…Combined analysis of the RAPID MI-ICE and the CHILL-MI trials also exhibited no difference in atrial fibrillation incidence ( 24 ). Within the temperature range used in STEMI cooling studies, no significant increase in ventricular arrhythmias has been reported ( 22 , 24 ), a finding consistent with animal studies ( 25 ). Taken together, mild TH seems not to significantly increase the occurrence of arrhythmia in general STEMI patients, but there could be a subpopulation of patients more prone to the development of arrhythmias, such as those with electrolyte dysregulation.…”
Section: Ecg Changes and Arrhythmias Associated With Thsupporting
confidence: 79%
“…After the completion of invasive procedures and a minimum of 15 min of stabilization, baseline values were obtained. Thereafter, CA was commenced by induction of ventricular fibrillation (VF) using programmed right ventricular stimulation as described previously [ 16 ]; mechanical ventilation was stopped during CA period. As shown in the protocol outline (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Although cardiac conduction is modified during therapeutic hypothermia, clinical studies show no significant increase in the risk of dysrhythmias when cooling to 32-35°C. [54][55][56][57] The first effect that therapeutic hypothermia has on cardiac function is a decrease in HR. 58 Recently, bradycardia during therapeutic hypothermia has even been associated with better outcomes.…”
Section: The Cardiac Pacemaker and Cardiac Conductionmentioning
confidence: 99%